High-achieving minority students can have more friends and fewer adversaries: Evidence from Hungary - Tamás Hajdu; Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
This study examines friendship and hostility relations between Roma students and the ethnically homogeneous non-Roma majority in Hungarian schools, where anti-Roma sentiments are strong. High-achieving Roma students have significantly more friends and fewer adversaries than low-achieving ones because of more non-Roma friends, fewer non-Roma adversaries, and the same number of Roma friends and adversaries. The associations are strong for publicly observable GPA but weak for unobserved test scores and may be the results of assignment to the same classes for many years. Simulations suggest that a mixed policy of desegregation and closing the achievement gap may best foster positive interethnic relations in this environment.
Keywords: J15; I24; 330; Social interactions; Minority students; Achievement gap